Electrophysiological correlates of emotional meaning in context in relation to facets of schizotypal personality traits: A dimensional study. Issue 3 (22nd December 2015) - Terrien, Sarah; Gobin, Pamela; Iakimova, Galina; Coutté, Alexandre; Thuaire, Flavien; Baltazart, Véronique; Mazzola‐Pomietto, Pascale; Besche‐Richard, Chrystel
Abstract : Aims: The aim of this study was to investigate the neurocognitive processes mediating the processing of emotional information during the integration of contextual and social information in a schizotypal population. Methods: One hundred and thirty‐one healthy participants were evaluated using the Schizotypal Personality Questionnaire and event‐related potentials were recorded during a linguistic task in which participants read sentence pairs describing short social situations to themselves. The first sentence implicitly conveyed the positive or negative emotional state of a character. The second sentence was emotionally congruent or incongruent with the first sentence. Results: Across our overall sample, our results revealed a greater N400 effect at right sites than left sites, whereas the late positive component effect was only observed at left sites. Concerning the correlation results, we observed a negative link between positive and global schizotypy and N400 modulation in response to congruent targets for positive context sentences. Results also showed a positive correlation between negative schizotypy and late positive component modulation in response to congruent targets for negative context sentences. Conclusions: These results suggest that the different facets of the schizotypal personality traits influenced the integration of emotional context at the level of both early and later‐mobilized neurocognitive processes.